Fat mass and obesity-associated protein expression in colorectal cancer and its influence on the biological behaviour of colorectal cancer cells - Huihui Wu; Yibo Wu; Zhishan Zhang; Qinglin Chen; Tingjin Zheng; Hui Zhong (Polish Journal of Pathology)
Fat mass and obesity-associated protein (FTO) was the earliest discovered m6A RNA demethylase. Previous studies have indicated that m6A modifications significantly influence the development, progression, and prognosis of various cancers. This study aimed to explore the role of FTO overexpression in colorectal cancer development, as well as its biological functions. Expression levels of FTO mRNA and protein in colorectal cancer and adjacent non-cancerous tissues were assessed using RT-PCR and immunohistochemistry. FTO overexpression was achieved by transiently transfecting an FTO overexpression plasmid into the HCT15 SW480 colorectal cancer cell line. The impact of this overexpression on the cells was evaluated using real-time fluorescence quantitative PCR, CCK8 proliferation assays, colony formation assays, scratch healing assays, and transwell migration and invasion assays. RT-PCR and immunohistochemistry demonstrated negligible or low FTO mRNA and protein expression in adjacent non-cancerous tissues, while high expression levels were observed in cancerous tissues. FTO overexpression in the HCT15 SW480 cell line significantly increased FTO mRNA levels compared to the control group. CCK8 assays indicated that cell proliferation was significantly higher in the FTO overexpressing group than in the control group. Colony formation assays revealed an increased number of colonies in the FTO group compared to controls. Scratch healing assays showed enhanced cell migration in the FTO group relative to controls. Transwell assays demonstrated a significant increase in invasive cell numbers in the FTO group compared to controls. In conclusion, FTO is highly expressed in colorectal cancer tissues, and its overexpression promotes proliferation and migration of colorectal cancer cells, underscoring its critical oncogenic role in this cancer type.